Comprehensive Study on Farmer Producer Organization in Idar Taluka, Gujarat - , Himan R. Patel, Dilip R. Vahoniya, Darshit B. Barvadiya (Archives of Current Research International, 2025)
The modernization of India’s agricultural sector is essential for realizing the vision of ‘Viksit Bharat’. Farmer Producer Organizations (FPOs) play a crucial role in empowering small, marginal, and landless farmers by enabling collective action and enhancing income opportunities. This study, conducted from January 26 to March 26, 2025, focuses on the Annadata FPO in Idar Taluka, Gujarat. The objectives were to examine the profile of the FPO, assess the socio-economic characteristics of its members, and identify the challenges faced by member farmers and the Board of Directors. Using a descriptive research design and purposive sampling, data were collected from 100 member farmers. Results indicated that 59% of the respondents were aged between 41 to 60 years, and 81% had only primary or secondary level education. In terms of income, 48% earned between ₹1–5 lakh annually. The most pressing organizational issue was lack of trust and conflicts among members (Garrett score: 58.30), followed by weak governance and leadership (51.65). Financial challenges included low financial literacy (52.92) and high interest rates (50.35). Key marketing constraints were limited awareness of market trends (55.66) and lack of branding and value addition (50.30). Input-related problems such as insufficient quantity (54.72) and high cost (49.64) were also prevalent. Major infrastructural issues included inadequate transportation (54.12) and storage facilities (52.48). For the Board of Directors, key concerns were poor leadership (5.58), inefficient logistics systems (5.94), and lack of business strategy awareness (5.58). The findings underscore the need for targeted interventions in capacity building, financial literacy, market integration, and infrastructure development to enhance the sustainability and impact of FPOs in rural India.